Are custom orthotics significantly more effective in reducing plantar pressure in patients with diabetes?. Issue 1 (January 2015) - Remde, Alan; Sandhu, Jyotu
Abstract : Evidence‐Based Answer : In patients with diabetes, custom orthotics significantly decrease plantar foot pressure compared with sham or no therapy (SOR: C, RCT, cohort, and case‐control trials with pressure outcomes).